2020
DOI: 10.1017/pasa.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

An ultra-wide bandwidth (704 to 4 032 MHz) receiver for the Parkes radio telescope

Abstract: We describe an ultra-wide-bandwidth, low-frequency receiver recently installed on the Parkes radio telescope. The receiver system provides continuous frequency coverage from 704 to 4032 MHz. For much of the band (∼60%), the system temperature is approximately 22 K and the receiver system remains in a linear regime even in the presence of strong mobile phone transmissions. We discuss the scientific and technical aspects of the new receiver, including its astronomical objectives, as well as the feed, receiver, d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(100 citation statements)
references
References 41 publications
0
94
0
1
Order By: Relevance
“…As a point of comparison, evaluating (14) for a Gaussian beam yields a survey speed of 0.721 G S 2 max , where G is the half power field of view of the Gaussian beam. Using this measure, the survey speed of ASKAP at 1.4 GHz is 245 times faster than the Parkes 64 m dish with a cryogenic single-pixel receiver having T sys /η of 40 k (Hobbs et al 2020).…”
Section: Survey Speedmentioning
confidence: 99%
“…As a point of comparison, evaluating (14) for a Gaussian beam yields a survey speed of 0.721 G S 2 max , where G is the half power field of view of the Gaussian beam. Using this measure, the survey speed of ASKAP at 1.4 GHz is 245 times faster than the Parkes 64 m dish with a cryogenic single-pixel receiver having T sys /η of 40 k (Hobbs et al 2020).…”
Section: Survey Speedmentioning
confidence: 99%
“….7-4.0 GHz) at at least one of our facilities in the near future (see Ransom et al 2019). Indeed, large fractional-bandwidth receivers have already been deployed by the PPTA (Hobbs et al 2020) and the EPTA (Freire 2012) for high-precision pulsar timing, and largefractional bandwidth or multi-band sub-arraying capabilities are either planned or are implemented in all of the aforementioned efforts.…”
Section: ∼0mentioning
confidence: 99%
“…Additionally, we note that Ziurys & Turner (1985) quote a velocity resolution 1.4 km s -1 , whereas our observations have a velocity resolution of 0.25 km s -1 . With the Parkes 64-m Telescope fitted with the new Ultra-wideband receiver (Hobbs et al 2020), we detected CH in the eastern lobe (IRS1) at 3.264 GHz in a 10min snapshot image. Therefore, we know the molecule to exist in the region, and more observing time should yield a detection of the low-frequency transitions.…”
Section: Results and Limits For Detectionmentioning
confidence: 99%
“…The CSIRO Parkes 64-m Telescope, an SKA technology pathfinder, has a new ultra-wide band receiver (Hobbs et al 2020), which covers the frequency range of 704-4 000 MHz, allowing simultaneous studies of the 724.788 MHz and ∼3.3 GHz CH transitions. Rydbeck et al (1973) observed CH ground state transitions at 3.264 GHz in 17 HII regions.…”
Section: Implications For Future Studiesmentioning
confidence: 99%